Ոսկյանների վկայաբանական զրույցի մատենագրական ու պատմական հենքը - Ազատյան, Շավարշ (Մատենադարան)
The legend about the Oskeans’ martyrdom was most probably written in the V-VI centuries. This text is of special significance for source study and historiography. On the basis of Tatian’s testimony and using folklore motifs, Armenian clergymen created a narrative which became widespread among the people who were still adherents of the pagan faith. The narration sheds light on certain issues related to the administrative structure of Armenia in the 5th–6th centuries. It also contributes to filling the gaps in the history of the spreading of Christianity. A number of historic data help us clarify some questions concerning the hierarchy of the Armenian Church. The legend also concerns social and political events of the early Middle Ages. It contains unique pieces of information on old settlements and on paganism in Ancient Armenia. Сказание о Воскянах, написанное, по всей вероятности в V–VI вв., имеет большую источниковедческую и историографическую ценность. Основываясь на свидетельстве Татиана, армянские священники, используя фольклорные мотивы, создали повествование, получившее широкое распространение в народе, еще не отошедшем от язычества. Повествование проливает свет на некоторые вопросы, касающиеся административного устройства средневековой Армении, а также способствует восполнению некоторых пробелов в истории распространения христианства. Ряд исторических данных дает возможность составить целостное представление о структуре армянской церкви. Повествование касается также некоторых социальных и политических событий раннего средневековья. Сказание содержит уникальную информацию о некоторых поселениях древней Армении, а также о языческых верованиях.
Keywords: Պատմություն